2017
DOI: 10.1038/srep42929
|View full text |Cite
|
Sign up to set email alerts
|

Absence of PD-L1 on tumor cells is associated with reduced MHC I expression and PD-L1 expression increases in recurrent serous ovarian cancer

Abstract: Immune-evasion and immune checkpoints are promising new therapeutic targets for several cancer entities. In ovarian cancer, the clinical role of programmed cell death receptor ligand 1 (PD-L1) expression as mechanism to escape immune recognition has not been clarified yet. We analyzed PD-L1 expression of primary ovarian and peritoneal tumor tissues together with several other parameters (whole transcriptomes of isolated tumor cells, local and systemic immune cells, systemic cytokines and metabolites) and compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 33 publications
2
46
1
Order By: Relevance
“…However, we cannot exclude an impact of pembrolizumab on other cell types including NK cells. Indeed, NK cell responses can have crucial immunotherapeutic effects upon PD-1/PD-L1 blockade in tumors with low levels of MHC-I expression [31]. Additional studies profiling functional immune cell responses during treatment with ICIs could bring new insights on the mechanism of these new therapies in the remission of cancer and viral diseases.…”
Section: Discussionmentioning
confidence: 99%
“…However, we cannot exclude an impact of pembrolizumab on other cell types including NK cells. Indeed, NK cell responses can have crucial immunotherapeutic effects upon PD-1/PD-L1 blockade in tumors with low levels of MHC-I expression [31]. Additional studies profiling functional immune cell responses during treatment with ICIs could bring new insights on the mechanism of these new therapies in the remission of cancer and viral diseases.…”
Section: Discussionmentioning
confidence: 99%
“…However, many cancer types exhibit a high incidence of MHC loss and/or low neoantigen burden (10,11), which should render tumor cells refractory to recognition by CD8 + T cells. High levels of PD-L1 expression have been observed in tumors with low MHC I expression (12)(13)(14)(15)(16)(17)(18). Interestingly, some of these cancer types are responsive to PD-1/PD-L1 blockade.…”
Section: Introductionmentioning
confidence: 99%
“…Although some authors 9 have confirmed the observation by Hamanishi et al, 8 others have shown exactly the opposite. [10][11][12] These controversial results have raised several questions regarding the method of determination, which types of cells should be scored for surface PD-L1 expression (tumor cell vs immune infiltrate vs both), and the best cutoff percentage of scored cells with which to determine PD-L1 positivity.…”
Section: Role Of Pd-l1 Expression In Patients With Ovarian Cancermentioning
confidence: 99%